2000
DOI: 10.1021/jp993285e
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formation of Nanoholes with (100)-Face Walls by Photoetching of n-TiO2 (Rutile) Electrodes, Accompanied by Increases in Water-Oxidation Photocurrent

Abstract: Nanometer-sized rectangular holes or grooves in the 〈001〉 direction were formed when single-crystal rutiletype n-TiO 2 (001), (110), and (100) electrodes were illuminated in 0.05 M H 2 SO 4 under anodic bias, accompanied by increases in water-oxidation photocurrents. Interestingly, only the (100) face was selectively exposed at the walls of the photoproduced holes and grooves, irrespective of crystal faces of electrode surfaces, though the (110) face for rutile TiO 2 is known to be the thermodynamically most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 33 publications
4
84
0
Order By: Relevance
“…20, a large number of rectangular porous holes shaped like wells, with a size of 50 -100 nm, emerged with a fairly regular arrangement. According to Sugiura et al 51) and Nakato et al, 52) rectangular holes proceed toward the h001i direction (c-axis direction), and the (100) face or equivalents are exposed selectively on the walls. This rectangular porous surface increased the sensitivity of the photoinduced hydrophilic reaction and achieved a high hydrophilicity under UV light irradiation of 1 mW/cm 2 , whereas the surface without a photoetching treatment did not, as shown in Fig.…”
Section: Photocatalysis In 21st Centurymentioning
confidence: 99%
“…20, a large number of rectangular porous holes shaped like wells, with a size of 50 -100 nm, emerged with a fairly regular arrangement. According to Sugiura et al 51) and Nakato et al, 52) rectangular holes proceed toward the h001i direction (c-axis direction), and the (100) face or equivalents are exposed selectively on the walls. This rectangular porous surface increased the sensitivity of the photoinduced hydrophilic reaction and achieved a high hydrophilicity under UV light irradiation of 1 mW/cm 2 , whereas the surface without a photoetching treatment did not, as shown in Fig.…”
Section: Photocatalysis In 21st Centurymentioning
confidence: 99%
“…21 Therefore, the design and synthesis of more efficient solar water splitting systems requires a deeper understanding of the water oxidation process; often considered a "kinetic bottleneck" in the overall water splitting reaction. 22 There have been several studies of the water oxidation reaction mechanism on TiO2, using electrochemical [23][24][25] and spectroscopic [26][27][28][29][30][31][32][33][34][35] methods, yet a detailed understanding of the reaction mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] Evidence for ̇ formation has been provided from diffuse reflectance FT-IR spectroscopy, 34 scanning tunneling microscopy 57 and by using spin trapping agents during electron paramagnetic resonance (EPR) spectroscopy. [31][32][33] The formation of these type of photo-generated holes is further detected by DFT calculations.…”
mentioning
confidence: 99%
“…For example, Nakato and coworkers have suggested that the (100) face of rutile TiO 2 possesses favorable properties for water oxidation. 173 Ohno and co-workers studied the role of the crystal faces of anatase and rutile TiO 2 particles in photocatalytic reactions. 174 It was suggested that the well-developed crystal faces help in the separation of electrons and holes in the TiO 2 particle.…”
Section: ¹1mentioning
confidence: 99%